Shear behavior degradation and failure pattern of reinforced concrete beam with chloride-induced stirrup corrosion. Issue 14 (October 2019) - Lu, Zhao-Hui; Li, Hai; Li, Wengui; Zhao, Yan-Gang; Tang, Zhuo; Sun, Zhihui
Reinforcement corrosion exhibits an adverse effect on the shear strength of reinforced concrete structures. In order to investigate the effects of chloride-induced corrosion of reinforcing steel on the shear behavior and failure pattern of reinforced concrete beams, a total of 24 reinforced concrete beams with different concrete strength grades and arrangements of stirrups were fabricated, among which 22 beams were subjected to accelerated corrosion to achieve different degrees of reinforcement corrosion. The failure pattern, crack propagation, load–displacement response, and ultimate strength of these beams were investigated under a standard four-point loading test in this study. Extensive comparative analysis was conducted to investigate the effects of the concrete strength, shear span-to-depth ratio, and stirrup type on the shear behavior of the corroded reinforced concrete beams. The results show that increasing the stirrup yielding strength is more effective in improving the shear strength of corroded reinforced concrete beams than that of concrete compressive strength. In terms of three types of stirrups, the shear strength of the beams with deformed HRB-335 is least sensitive to stirrup corrosion, followed by the beams with smooth HPB-235 and the beams with deformed HRB-400. The effect of the different stirrups on the shear strength depends on the corrosion degree of stirrup and shear span-to-depth ratio of the beam. The predicted results of shear strength of corroded reinforced concrete beams by a proposed analytical model are well consistent with the experimental results.